Free and Substrate-Immobilised Lipases from Fusarium verticillioides P24 as a Biocatalyst for Hydrolysis and Transesterification Reactions - Borges, Janaina Pires [UNESP]; Quilles Junior, José Carlos [UNESP]; Ohe, Thiago Hideyuki Kobe [UNESP]; Ferrarezi, Ana Lucia [UNESP]; Nunes, Christiane da Costa Carreira [UNESP]; Boscolo, Mauricio [UNESP]; Gomes, Eleni [UNESP]; Bocchini, Daniela Alonso [UNESP]; da Silva, Roberto [UNESP] (Springer Nature, 2020)
Fungal enzymes are widely used in technological processes and have some interesting features to be applied in a variety of biosynthetic courses. Here, free and substrate-immobilised lipases from Fusarium verticillioides P24 were obtained by solid-state fermentation using wheat bran as substrate and fungal carrier. Based on their hydrolytic and transesterification activities, the lipases were characterised as pH-dependent in both reactions, with higher substrate conversion in an alkaline environment. Thermally, the lipases performed well from 30 to 45 °C, being more stable in mild conditions. Organic solvents significantly influenced the lipase selectivity using different vegetable oils as fatty acid source. Omega(ω)-3 production in n-hexane achieved 45% using canola oil, against ≈ 18% in cyclohexane. However, ω-6 production was preferably produced for both solvents using linseed oil with significant alterations in the yield (≈ 79% and 49% for n-hexane and cyclohexane, respectively). Moreover, the greatest enzyme selectivity for ω-6 led us to suppose a lipase preference for the Sn1 position of the triacylglycerol. Lastly, a transesterification reaction was performed, achieving 90% of ester conversion in 72 h. This study reports the characterisation and use of free and substrate-immobilised lipases from Fusarium verticillioides P24 as an economic and efficient method for the first time.
Keywords: Fusarium verticillioides; Hydrolysis; Lipase; Omega-3; Omega-6; Transesterification